2010
DOI: 10.1248/bpb.33.398
|View full text |Cite
|
Sign up to set email alerts
|

Low Direct Cytotoxicity of Loxoprofen on Gastric Mucosal Cells

Abstract: Non-steroidal anti-inflammatory drugs (NSAIDs), such as indomethacin, are a useful family of therapeutics.1) An inhibitory effect of NSAIDs on cyclooxygenase (COX) activity is responsible for their anti-inflammatory actions because COX is an enzyme essential for the synthesis of prostaglandins (PGs), such as PGE 2 , which have a strong capacity to induce inflammation. On the other hand, NSAID use is associated with gastrointestinal complications. [2][3][4] In 1991, two subtypes of COX, COX-1 and COX-2, which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…4, 5) is needed to achieve this prevention. The results support the previously reports showing that loxoprofen has relatively lower membrane permeabilization activities and cytotoxic effects on gastric mucosal cells than other NSAIDs, [21][22][23] since the gastric lesion score and concentration of Mg 2+ to prevent loxoprofen-induced gastric lesions in AA rats are lower than those of indomethacin. 24) In addition, we have demonstrated the effect of magnesium ion on loxoprofen absorption in AA rats.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…4, 5) is needed to achieve this prevention. The results support the previously reports showing that loxoprofen has relatively lower membrane permeabilization activities and cytotoxic effects on gastric mucosal cells than other NSAIDs, [21][22][23] since the gastric lesion score and concentration of Mg 2+ to prevent loxoprofen-induced gastric lesions in AA rats are lower than those of indomethacin. 24) In addition, we have demonstrated the effect of magnesium ion on loxoprofen absorption in AA rats.…”
Section: Discussionsupporting
confidence: 91%
“…Loxoprofen is a pro-drug that is converted (by reduction of the cyclopentanone moiety) to its active metabolite (the trans-alcohol metabolite of loxoprofen) by aromatic aldehyde-ketone reductase only after absorption into the gastrointestinal tract, 20) and loxoprofen has relatively lower membrane permeabilization activities and cytotoxic effects on gastric mucosal cells than other NSAIDs. 21) Based on these findings, loxoprofen is suggested to be safer than other NSAIDs, such as indomethacin. 22,23) However, even loxoprofen causes gastroenteropathy as a clinical side effect.…”
mentioning
confidence: 99%
“…In Japan, osteoporosis is usually treated by medical practitioners of orthopaedic surgery. Many patients visit them for pain as a primary physical complaint, and therefore are very often prescribed with antipyretic analgesics, especially loxoprofen, which is the most frequently prescribed drug in Japan [8,9]. If this study proves that loxoprofen reduces the incidence and severity of APRs, like ibuprofen, the majority of patients will not need an additional prescription for loxoprofen, because the likelihood is high that their orthopaedic surgeons have already prescribed loxoprofen at the initial visit.…”
Section: Resultsmentioning
confidence: 92%
“…Compared to other NSAIDs, such as indomethacin and celecoxib, loxoprofen showed less membrane permeability and low direct cytotoxicity, and therefore lower incidence of NSAIDs-induced gastroenteropathy [8]. Loxoprofen is also the NSAID most often prescribed by orthopedists in Japan [9].…”
Section: Introductionmentioning
confidence: 99%
“…23 We recently reported that loxoprofen has lower membrane permeabilization activity than other NSAIDs. 24 Therefore, synthetic modification of loxoprofen to either increase specificity for COX-2 or decrease membrane permeabilization activity is a valuable strategy to obtain safer NSAIDs.…”
Section: Introductionmentioning
confidence: 99%